Management of Information Resources in Federal High Court Libraries in North-East Geo-Political Zone of Nigeria - Barkindo, Amina; Abubakar , Bappah Magaji (MiddleBelt Journal of Library and Information Science, 2021)
Library is the knowledge base of any organization that provides information resources and services for the planning, research, training, production and development of the parent organization. Special libraries achieve this through proper management in line with the vision and mission of the parent organization. The objectives of the study were to find out how the federal high court libraries in North-eastern Nigeria provide information resources, the procedures for the management and the challenges associated with the provision and management of the information resources in these libraries. Qualitative research method, using narrative-based research design was adopted for the study while interview guide was the instrument used for data collection. Five heads of the libraries were purposely selected to serve as the study participants from five (5) Federal High Courts in the zone. The data collected was analyzed thematically using coding system. The findings revealed that the librarians in charge of the libraries had minimal control over the provision of information resources in terms of selection and acquisition. It further showed that the resources were organized serially in accordance with the broad subject of each item on the open shelves without the provision of any class mark on the books. It therefore concludes that the situation of libraries was below the standard expected and thus, leaves much to be desired. The study therefore recommends that budgetary allocation to judicial libraries should be enhanced so as to provide relevant and adequate resources and information and communication technologies for effective and efficient library services.